2018
DOI: 10.1158/2326-6066.cir-18-0309
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Neutralized Reovirus Is Effective in Oncolytic Virotherapy

Abstract: Immunotherapy is showing promise for otherwise incurable cancers. Oncolytic viruses (OVs), developed as direct cytotoxic agents, mediate their antitumor effects via activation of the immune system. However, OVs also stimulate antiviral immune responses, including the induction of OV-neutralizing antibodies. Current dogma suggests that the presence of preexisting antiviral neutralizing antibodies in patients, or their development during viral therapy, is a barrier to systemic OV delivery, rendering repeat syste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 22 publications
1
48
0
Order By: Relevance
“…However, pre-existing anti-measles immunity did not affect anti-CHIKV immune responses in human subjects [10]. In the context of oncolytic virotherapy, pre-existing anti-viral immunity may even be conducive to anti-tumor efficacy [21,71,72].…”
Section: Discussionmentioning
confidence: 98%
“…However, pre-existing anti-measles immunity did not affect anti-CHIKV immune responses in human subjects [10]. In the context of oncolytic virotherapy, pre-existing anti-viral immunity may even be conducive to anti-tumor efficacy [21,71,72].…”
Section: Discussionmentioning
confidence: 98%
“…113 Furthermore, antibodyneutralized reovirus complex can be introduced into human monocytes, where internalized complexes were processed to release infectious particles, ultimately targeting cancer cells. 114 Mesenchymal stem cells (MSCs) have been used as a delivery system for chimeric human ade-novirus5/3 (HAdV5/3) with the primary purpose of masking the virus from immune attack. 115 The cellular receptor for HAdV5 entry, coxsackievirus and adenovirus receptor (CAR) is poorly expressed in MSCs.…”
Section: Cell Carriersmentioning
confidence: 99%
“…Another example for use of bifunctional adapters arises from a recent study on oncolytic adenovirus hTert-Ad treatment in combination with DE1scFv-pSia protein containing a DE1 domain of adenovirus hexon and a polysialic acid-specific single-chain variable fragment (scFv) to capture neutralizing antibodies and for tumor cell recognition, respectively. 125 • In vivo study against lung cancer 111 • In vivo study against metastatic melanoma 112,113 • In vivo study against melanoma 114 • In vitro study against pancreatic cancer 115 • In vivo study against ovarian cancer 131…”
Section: Other Strategiesmentioning
confidence: 99%
“…Intriguingly, it was also shown that when human monocytes were loaded with preformed reovirus-antibody complexes (neutralizing the reovirus) they were able to deliver fully replication competent reovirus to tumor cells in vitro. In vivo administration of neutralized reovirus-antibody complexes were also shown to slow B16 mouse melanoma tumor growth compared to vehicle only [163]. A range of cell types have been used as cell carriers for variety of OV and the preclinical success of these have been well reviewed by Roy et al [164] Determining which cell is best to use for different tumor indications is an important consideration when implementing carrier cell systems.…”
Section: Cell Carriersmentioning
confidence: 99%